2020
DOI: 10.1007/s11769-020-1097-0
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Air Temperature and Relative Humidity on Building Areas and in Green Spaces in Beijing, China

Abstract: The cooling and humidifying effects of urban parks are an essential component of city ecosystems in terms of regulating microclimates or mitigating urban heat islands (UHIs). Air temperature and relative humidity are two main factors of thermal environmental comfort and have a critical impact on the urban environmental quality of human settlements. We measured the 2-m height air temperature and relative humidity at the Beijing Olympic Park and a nearby building roof for more than 1 year to elucidate seasonal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 77 publications
1
12
1
Order By: Relevance
“…For example, the average value of RH during October in Beijing (China) in the park is about 54% in the afternoon, while at the city square, RH was lower (43%). Thus, the difference in RH between locations was about 11% during the daytime, but as the day went on, the differences became more pronounced (20%) (Kuang, 2020). A similar observation can be seen in the city of Novi Sad.…”
Section: Relative Humiditysupporting
confidence: 69%
See 1 more Smart Citation
“…For example, the average value of RH during October in Beijing (China) in the park is about 54% in the afternoon, while at the city square, RH was lower (43%). Thus, the difference in RH between locations was about 11% during the daytime, but as the day went on, the differences became more pronounced (20%) (Kuang, 2020). A similar observation can be seen in the city of Novi Sad.…”
Section: Relative Humiditysupporting
confidence: 69%
“…The urban park had a lower temperature compared to the city square during the whole measurement, while compared to the urban street, it had a lower value of Ta only after 2 p.m. Our results are generally in line with other intra-urban micrometeorological studies. For example, in Beijing (China) the difference in Ta between the park (vegetation) and the street (buildings) was about 1.24 o C during daytime (Kuang, 2020), while in Novi Sad the average Ta difference between these two locations was less severe (only about 0.4 o C). These differences may vary because of the measurement period, urban form or even the human activities during the day.…”
Section: Air Temperaturementioning
confidence: 99%
“…H. Du et al (2021) conducted microclimate field measurements on 35 gas storage reservoirs in Shanghai, China, and investigated the effect of urban green space on temperature through data collection and statistical analysis, eventually found that the shape of the urban green space had a significant effect on the temperature and humidity index (THI). Kuang (2020) measured air temperature and relative humidity at 2 m height on the roofs of the Beijing Olympic Park and nearby buildings for more than 1 year. The results indicate that the cooling and humidifying effects of urban parks are an important component of urban ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…erefore, it can be seen that the fragmentation of GI components caused by the rapid urbanization is also the cause for their evolution from large-scale development and centralization toward the direction of the network. e urban GI can be guided to a more resilient trajectory and made conducive for the improvement of urban resilience if the opportunity can be seized and scientifically reasonable protection measures are taken [61]. is radically changes our understanding of a larger green space being more suitable for an optimized pattern and function contributing toward the resilient development of the city.…”
Section: E Implication Of Rapid Urbanization On the Changes Of Gimentioning
confidence: 99%